1967
DOI: 10.1139/f67-083
|View full text |Cite
|
Sign up to set email alerts
|

Limnetic Larval Fish in Northern Wisconsin Lakes

Abstract: The open water of two northern Wisconsin lakes was sampled for larval fish at night with fine-mesh conical townets. Those collected were identified to genus or species and enumerated. The majority of larval fish were captured in the limnetic region but a few never strayed from the littoral region.The seasonal changes of the limnetic species were similar for the two lakes and 3 years of study. Their abundance varied greatly from year to year but yellow perch, sunfish, and black crappies always dominated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The appearance of these could be corprevious workers (Faber 1967, Noble 1970 found related with the maturing of successive batches of that the larvae aggregate less during darkness. The eggs in the female ovaries (unpublished data).…”
Section: Netting and Processing Proceduresmentioning
confidence: 79%
“…The appearance of these could be corprevious workers (Faber 1967, Noble 1970 found related with the maturing of successive batches of that the larvae aggregate less during darkness. The eggs in the female ovaries (unpublished data).…”
Section: Netting and Processing Proceduresmentioning
confidence: 79%
“…In contrast, no shoaling behaviour was observed in May. At this time the transparency of perch larvae (Ward & Robinson, 1974;Coles, 1981;Wang & Eckmann, 1994) is supposed to be sufficient adaptation for life in the pelagic zone of lakes and reservoirs, since they are thus invisible to predators (Faber, 1967). However, in their classical study, Thetmeyer & Kils (1995) have demonstrated that transparent organisms may also be highly visible and detectable by predators, due to light absorbance by opaque parts of the body or light scattered in the tissues, and Čech & Kubečka (2002) have suggested that the sinusoidal cyclic swimming of fish may be a mechanism effectively eliminating the advantage gained by transparent prey.…”
Section: Discussionmentioning
confidence: 97%
“…It is widely accepted that perch larvae migrate from near-shore spawning sites into the pelagic area soon after hatching (Whiteside et al, 1985;Post & McQueen, 1988;Treasurer, 1988;Wang & Eckmann, 1994) where, owing to their transparency (Ward & Robinson, 1974;Coles, 1981), they are probably less vulnerable to predation (Faber, 1967). Perch fry are reported to stay in the pelagic zone for a month, or longer, and after metamorphosis, when pigmented juveniles are more susceptible to predation in the offshore habitat, they return to the littoral area (Ward & Robinson, 1974;Coles, 1981;Whiteside et al, 1985;Treasurer, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…1), another gyre moves in a clockwise direction, i.e., currents return to the eastern part of the lake (Le Thi et al, 2012). After hatching, perch larvae are pelagic until reaching 2 cm in length (2 months) (Faber, 1967). Then, they move into the pelagic zone to feed on zooplankton (Wang and Eckman, 1994).…”
Section: Discussionmentioning
confidence: 99%